Woman arriving in the streets of Dawson with a dog team carrying her luggage, Yukon Territory, 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "Dog team express Dawson City 98" Original photograph by Eric A. Hegg 2467; copied by Larss and Duclos